RENEWABLE SOCIO-ECONOMIC INCLUSION IN PREDICTING ECONOMIC SUSTAINIBILITY: EMPIRICAL ANALYSIS FROM INDONESIA - Ariyani, Diyah; Bahjatulloh, Qi Mangku; Purwaningrum, Devvy Ayu; Sifaudin, Muhammad (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
The study aims to identify various sustainable initiatives undertaken by Indonesia's manufacturing and services industry, which examines the 50 largest companies listed on the IDX. Furthermore, this study shows the impact of Social Sustainibility (SS), Environmental Sustainibility (Env-S), Financial Sustainibility (FS) on Economic Sustainibility (ES) with financial performance as a variable control. This study uses a descriptive quantitative design method and clause. The sample consists of a series of time series data on the results of reporting on the disclosure of environmental conservation responsibilities of companies listed on the IDX and data for the last 24 years of Foreign Investment (PMA) and Domestic Investment (PMDN). Multiple linear regression analysis was used to test the influence of SS, Env-S, FS on economic sustainability. FS, which is a variable control, is intended as a constant variable to minimize the influence of other variables. The main findings of this study are that director policies and donations have a significant positive influence on the financial sustainability of companies; However, the green house and climate bond factors were not found to have a significant sustainability impact and the results were negative; Then, the domestic credit and ATM factors have a significant positive impact on sustainability on the Employee's utilization ratio and the Human Development Index. The implications of this study have been classified into factual novelty categories; The implications of the theorical environmental ethic, practical managerial and policy brief of the green economy to encourage the sustainability of the national economy.